Korelasi Komunikasi Digital Hindu di TikTok dengan Visi Indonesia Emas 2045 - Chandra, Edy Chandra; Prabawa, Bagus Ade Tegar (Widya Duta: Jurnal Ilmiah Ilmu Sosial Budaya, 2025)
This study aims to examine the extent of the correlation between digital communication based on Hindu teachings in supporting the achievement of Indonesia's Golden Vision 2045 through the TikTok app. The approach used in this study is a quantitative method with a survey technique, involving a sample of 40 respondents whose data were collected via questionnaires. The data analysis results show a significant relationship between digital communication based on Hindu teachings (X) and the achievement of Indonesia's Golden Vision 2045 (Y), as evidenced by a significance value of 0.013, which is smaller than the table significance value of 0.05. Additionally, the correlation coefficient between variables X and Y is 0.388, which is greater than the table correlation value of 0.301. Based on these results, the null hypothesis (H0) is rejected, and the alternative hypothesis (H1) is accepted, confirming the existence of a correlation between digital communication based on Hindu teachings and the achievement of Indonesia's Golden Vision 2045 through TikTok. The findings of this study are expected to serve as a recommendation for the Hindu community to become more active in utilizing the digital world as a medium for spreading religious teachings, in order to support Indonesia's Golden Vision 2045 and instill spiritual and character values in society.